Ergonomics problems in dental profession-dentists working position - Pejčić Nataša; Petrović Vanja; Dimitrijević-Jovanović Nina; Rakić Mia; Đurić-Jovičić Milica; Poštić Srđan; Perunović Neda (Balkan Stomatological Society, 2022)
Background/Aim: Dental professionals are under higher risk of development musculoskeletal disorders. Working in unnatural position is one of the main risk factor for the development of MSDs. The aim of study was to record inclinations of the back in dentists during typically dental work. Material and Methods: In order to monitor the inclination of the body, high-performance sensor systems, triaxial digital 12-bit accelerometers LIS3LV02 (SGS-Thomson Microelectronics, USA) were installed. The inclination of the body was measured in ten dentists, while performing dental work. Results: During dental work in a sitting position, sloping back more than 20 ̊ was during 74% of the time, while during standing 62% of the time. The participants performed the dental examination sloping to the left side. During sitting, the inclination to the left side was greater than 20 ̊ during 65% of the time, while during work in the standing position it was 50%. Conclusions: An inclination of the back, more than 20 degrees is state as one of the main risk factor for the development of MSD. Inclination of the dentist's body in antero-posterior and medio-lateral direction during daily work in standing as well in sitting position was greater than 20 degrees. According to those facts dentists are under risk of developing musculoskeletal diseases during their daily working procedure. According to that ergonomics in dentistry is an area of research that needs more attention. The implementation of ergonomic principles in usual dental work leads to increased work performance, greater satisfaction, efficiency and productivity